Analytical applications of single particle inductively coupled plasma mass spectrometry: a comprehensive and critical review. Issue 25 (23rd June 2021) - Bolea, Eduardo; Jimenez, Maria S.; Perez-Arantegui, Josefina; Vidal, Juan C.; Bakir, Mariam; Ben-Jeddou, Khaoula; Gimenez-Ingalaturre, Ana C.; Ojeda, David; Trujillo, Celia; Laborda, Francisco
Abstract : Real-world applications of single-particle ICP-MS are comprehensively and critically reviewed. Abstract : Single particle inductively coupled plasma mass spectrometry (SP-ICP-MS) refers to the use of ICP-MS as a particle counting technique. When ICP-MS measurements are performed at very high data acquisition frequencies, information about (nano)particles containing specific elements and their dissolved forms can be obtained (element mass per particle, size and number and mass concentrations). As a result of its outstanding performance, SP-ICP-MS has become a relevant technique for the analysis of complex samples containing inorganic nanoparticles. This review discusses the maturity level achieved by the technique through the methods developed for the detection, characterisation and quantification of engineered and natural (nano)particles. The application of these methods in different analytical scenarios is comprehensively reviewed and critically discussed, with special attention to their current technical and metrological limitations. The emergent applications of SP-ICP-MS in the field of nanoparticle-tagged immunoassay and hybridization methods are also reviewed.